Minority ethnicity patient satisfaction and experience: results of the National Cancer Patient Experience Survey in England. Issue 6 (28th June 2016) - Pinder, Richard J; Ferguson, Jamie; Møller, Henrik
Abstract : Objectives: This study sought to explore the differential patient satisfaction reported by patients with cancer who are from ethnic minority backgrounds, examining patient-reported experience of interacting with medical and nursing staff. Setting: As a secondary analysis, we collated data collected over two consecutive annual rounds of the National Cancer Patient Experience Survey (NCPES) from September 2012 to November 2013. Participants: There were 138 878 responses from 155 hospital trusts across the National Health Service in England, representing a response rate of 63.9% based on the total identified cohort of patients receiving cancer care over those 2 years. Outcomes: We used the results of the annual survey, which sought to assess overall patient satisfaction along with patient experience of interacting with clinical nurse specialists, hospital doctors and ward nurses. Results: Ethnic minority patients reported lower satisfaction and less positive experiences of care overall. While some of this difference appeared related to demographic and socioeconomic variation, ethnic minority patients remained less positive than those in the White British group, after statistical adjustment. Ethnic minority patients also reported lower confidence in, and less understanding of, healthcare professionals, including clinical nurse specialists, doctors and ward nurses. Conclusions: Given the diversity of the British population, as well as the clustering of ethnic minority patients in certain urban areas, a better understanding of the expectations and additional needs of ethnic minority patients is required to improve their experience of and satisfaction with cancer care.